Informal Learning and Non-Formal Education for Development - Colin Robert Latchem (Commonwealth of Learning, 2013)
The following article examines the issues of open, distance and technology-based informal learning and non-formal education for individual and community development. It argues that these two modes of education, which are estimated to constitute 70-90% of lifelong learning, are insufficiently represented in the literature of open and distance learning and development. To ensure that these forms of provision take their rightful place alongside the mainstream systems of formal education, it is posited that far more research and evaluation is needed in order to demonstrate their potential and evidence quality in their outputs, outcomes and impacts.